TEKNOLOGI FARM MANAGEMENT SYSTEM UNTUK MENDUKUNG BUDIDAYA PERTANIAN BERKELANJUTAN - Khoirul Bariyyah; Ahmad Hadi; Ni’mawati Sakinah; Putri Istianingrum; Annastia Loh Jayanti; Kanthi Pangestuning Prapti; Shinta Hiflina Yuniari; Moh. Fahrurrozi (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2023)
FMS technology is a digital platform designed to collect environmental information on plant growth, microclimate monitoring and automation of fertilization and irrigation of cultivated plants. The FMS application has 4 main functions, namely land digitization, soil nutrient condition monitoring system (agrooscane), climate monitoring system (agrooclimate), monitoring and automation of fertilization and irrigation (agroomation). This study aims to determine the effectiveness of using agroscan, agroclimate, and agroomation tools on cultivated land in Kumendung Village, Muncar District, Banyuwangi Regency. This research method uses the experimental method. The results of the study, namely the FMS agroscan technology, are effectively used to recommend improving soil pH, adding N, P, and K fertilizer inputs according to the needs of cultivated plant commodities. FMS agroclimate technology, effective for monitoring microclimate (temperature, humidity, rainfall, irradiation duration, and wind speed). The data displayed in the FMS agrooclimate can be used for consideration in determining crop timing, using varieties resistant to pests and diseases that develop in cultivation environments, crop rotation, fertilizing and irrigation times. FMS Agroomation technology is effectively used for setting fertilization and irrigation schedules.